2019
DOI: 10.3389/fimmu.2018.03132
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 and T-Bet in Immunopathogenesis of Ankylosing Spondylitis—Novel Targets for Therapy?

Abstract: Susceptibility to ankylosing spondylitis (AS) is polygenic with more than 100 genes identified to date. These include HLA-B27 and the aminopeptidases (ERAP1, ERAP2, and LNPEPS), which are involved in antigen processing and presentation to T-cells, and several genes (IL23R, IL6R, STAT3, JAK2, IL1R1/2, IL12B, and IL7R) involved in IL23 driven pathways of inflammation. AS is also strongly associated with polymorphisms in two transcription factors, RUNX3 and T-bet (encoded by TBX21), which are important in T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…These findings might enlighten us on the importance of ILCs in the pathogenesis of SpA. Runx3 is a pivotal transcription factor that induces RORγt and AHR, which guides the differentiation of ILC3 precursors to IL-17A and IL-22 expressing mature ILC3 (159). The transcription factor Tbet has already been found to be crucial in the development and differentiation ILC1.…”
Section: Spondyloarthritismentioning
confidence: 85%
“…These findings might enlighten us on the importance of ILCs in the pathogenesis of SpA. Runx3 is a pivotal transcription factor that induces RORγt and AHR, which guides the differentiation of ILC3 precursors to IL-17A and IL-22 expressing mature ILC3 (159). The transcription factor Tbet has already been found to be crucial in the development and differentiation ILC1.…”
Section: Spondyloarthritismentioning
confidence: 85%
“…The common mechanisms from these networks revealed several lymphoid and myeloid cells and their expressing DAGs. The lymphoid cells such as CD4 + Th1, CD4 + Treg, and NK were predominant in all the statistically significant common-cell gene networks, showing that these diseases were indeed mainly driven by the aggressive T-cell response (36)(37)(38)55). Pathways such as interleukin (IL-4 and IL-13), TLR, TCR signaling, etc., was found to be enriched in the top DAGs of the common cell-gene networks of these IMIDs.…”
Section: Common Cell-gene Network Reveal Drug Repurposing Targetsmentioning
confidence: 97%
“…We find RUNX3 expression highest in the NK cells, followed by CD8 + Tcells and Th1 cells (Supplementary Figure S1A). The exact role of RUNX3 in AS is unclear and possibly involves regulation, differentiation, and activation of Th1 and T-bet cells (36). Further research is required to establish the exact role of RUNX3 in AS and the above-identified lymphoid cell subsets.…”
Section: The Disease-gene Network Of the 12 Imids Reveal Several Common Dagsmentioning
confidence: 99%
“…Finally, deletions in RUNX3 gene can also result in malignancies of T cells (217). Among the phenotypes associated with polymorphisms in the RUNX3 gene locus are ankylosing spondylitis (218)(219)(220), psoriatic arthritis (221), Crohn disease (222), asthma (223) and multiple sclerosis (224). In B cells, RUNX3 is upregulated by the Epstein-Barr virus-encoded TF EBNA2, leading to accelerated proliferation of infected cells (225).…”
Section: Runx3mentioning
confidence: 99%